Marbling Texture Has No Effect on Collagen Characteristics - B. A. Olson; K. R. Vierck; J. M. Gonzalez; J. A. Noel; T. A. Houser; E. A. Boyle; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:The objective of this study was to determine the effects of marbling texture on collagen traits and adipocyte cross-sectional area. Study Description:Beef strip loins (n = 117) from three U.S. Department of Agriculture quality grades (Top Choice, Low Choice, and Select) with three marbling textures (fine, medium, and coarse) were selected using visual appraisal. Strip loins were taken to the Kansas State University meat laboratory, Manhattan, KS, fabricated into 1-in steaks, vacuum packaged, and aged for 21 days at 40°F. Following aging, steaks were analyzed for collagen and adipocyte staining, imaging, and peak thermal transition temperature. The Bottom Line:These results indicate that marbling texture has no effect on collagen traits and any potential tenderness differences among beef varying in marbling texture are not related to these traits.
Keywords: adipocyte; collagen; marbling texture